Identification of Cryptococcus neoformans isolates using Staib agar without creatinine - Nardelli Vanessa; Pérez Celina; Mata-Essayag Sofía; Colella María Teresa; Roselló Arantza; Hartung de Capriles Claudia; Landaeta María Eugenia; Olaizola Carolina; Magaldi, Sylvia (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2005)
Abstract: In mycology, culture is the best way to demonstrate and identify pathogenic fungi. Many kinds of media have been developed and modified, using fungal biochemical properties to recognize them. The most common media are Sabouraud, Malt Agar, Cornmeal agar, Potato-dextrose agar, and Staib agar. Staib agar has been widely used for identification of yeasts from the genus Cryptococcus and other fungi. The aim of this study was to demonstrate the usefulness of Staib agar, and of a modified Staib medium without creatinine, in the isolation and identification of fungi. Forty-six Cryptococcus neoformans strains plus one control strain was identified by morphological and biochemical criteria, using urease test (Christensen urea agar) and culture in Sablac medium. The strains were then transferred into standard Staib and Staib without creatinine agar plates. Morphological features and phenoloxidase production were evaluated after one-week incubation at room temperature (26-28°C). Culture in standard and modified Staib agar yielded brown color colonies (phenoloxidase production) in both media in 43 (91.5%) cases. Staib agar without creatinine is an excellent medium for identification of C. neoformans, with the advantage of a low cost and easy preparation. Resumen: En micología, el cultivo es la mejor manera de realizar el diagnóstico definitivo de una micosis. Muchos tipos de medios han sido desarrollados y modificados para tal fin, utilizando las propiedades bioquímicas de los hongos para reconocerlos. Los medios más comunes son Sabouraud, agar Malta, agar maíz, agar Papa-dextrosa, y agar Staib. Este último ha sido ampliamente usado para la identificación de levaduras del género Cryptococcus y en otros hongos. El objetivo de este estudio fue demostrar la utilidad del agar Staib y de un medio de Staib modificado, sin creatinina, en el aislamiento e identificación de hongos patógenos. Cuarenta y seis aislados de Cryptococcus neoformans más un control fueron identificados por criterios morfológicos y bioquímicos, usando la prueba de ureasa (agar urea de Christensen) y cultivo en medio Sablac. Las cepas fueron transferidas a placas de agar Staib estandar y de agar Staib sin creatinina. Las placas fueron incubadas a temperatura ambiente (26-28°C) durante una semana y luego fueron evaluadas las características morfológicas de las colonias y producción de fenoloxidasa. En 43 (91.5%) de las cepas estudiadas, se observó producción de fenoloxidasa (presencia de colonias marrones) tanto en el agar estandar como en el agar sin creatinina. Conclusión: el agar Staib sin creatinina es un medio excelente para la identificación de C. neoformans, con las ventajas de un bajo costo y fácil preparación.